Assessment of Lead (Pb) Bioaccumulation in Seluang Fish (Rasbora sp.) and Water Quality Analysis in Miai Riverysis of Lead (Pb) levels in Seluang Fish (Rasbora Sp) in the Miai River in Banjarmasin City - Azzahra, Yenni; Santoso, Heri Budi; Muhamat, Muhamat (Jurnal Biologi Tropis, 2025)
The waters of the Miai River are located in a densely populated residential area with a variety of household activities and landfills (TPS), one of which is hazardous waste containing heavy metals. Heavy metal lead (Pb) is dangerous because it is toxic. The study's objectives were to quantify the lead concentration in seluang fish and water and ascertain the correlation between fish weight and lead levels in water. The Miai River's waters served as the site of the study. Purposive sampling was used to collect water and seluang fish samples. The Pb concentration was determined using an Atomic Absorption Spectrophotometer (AAS) after samples were collected from two stations three times. The results of Pb content in river water at station 1 averaged around 0.00589 mg/L and station 2 averaged around 0.00690 mg/L and the results of Pb levels in seluang fish at station 1 averaged around 0.00333 mg/kg and station 2 averaged around 0.00600 mg/kg. This means that river water and seluang fish are contaminated with Pb but still below the quality standards set, so they can still be utilized according to their designation and are still safe for consumption. The relationship between Pb in fish and fish weight shows a correlation coefficient of r = -0.598, meaning that the correlation is unidirectional and Pb in water with Pb in fish correlates r = 0.439, indicating a relationship with a moderate level.